النظام القانوني الدولي لمنطقة الجرف القاري - جامع, شادي; غزال, عبد اللطيف (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The continental shelf is one of the areas of great economic importance in the international law of the sea ,The legal regime of this area has evolved in several stages, both in international conventions (Convention on the Continental Shelf. 1958 and the United Nations Convention on the Law of the Sea. 1982) Or through decisions of international tribunals in international disputes relating to this region, This research will discuss the evolution of the international legal regime of the continental shelf area in terms of its origin, its limits and the rights and obligations of States on it , We will also analyze conflicts related to the opposite or adjacent coasts, and then review the methods provided by international law for the pacific settlement of these disputes , and summarize the most important principles and rules agreed upon in this regard. تعتبر منطقة الجرف القاري من المناطق التي تحتل أهمية اقتصادية كبيرة في القانون الدولي للبحار , وقد تعرض النظام القانوني لهذه المنطقة لتطورات متلاحقة , سواء في الاتفاقيات الدولية (اتفاقية الجرف القاري لعام 1958 واتفاقية الأمم المتحدة لقانون البحار لعام 1982 ) التي نظمت أحكامها أو من خلال أحكام القضاء الدولي في معرض حله للنزاعات المتعلقة بهذه المنطقة بين الدول , وسوف يتناول هذا البحث تطور النظام القانوني الدولي لمنطقة الجرف القاري من حيث نشأته ومن حيث امتدادات هذه المنطقة وحقوق الدولة عليها , والاشكالات التي تثيرها هذه الامتدادات في حالات سواحل الدول المتقابلة أو المتلاصقة , ومن ثم نتعرض للآليات المقررة في القانون الدولي لحل هذه الاشكالات والنزاعات الدولية, وأهم المبادئ والحلول التي تم التوصل اليها بهذا الشأن .